2011
DOI: 10.1039/c1cp20173e
|View full text |Cite
|
Sign up to set email alerts
|

Direct electro-deposition of graphene from aqueous suspensions

Abstract: We describe the direct electro-chemical reduction of graphene oxide to graphene from aqueous suspension by applying reduction voltages exceeding -1.0 to -1.2 V. The conductivity of the deposition medium is of crucial importance and only values between 4-25 mS cm(-1) result in deposition. Above 25 mS cm(-1) the suspension de-stabilises while conductivities below 4 mS cm(-1) do not show a measurable deposition rate. Furthermore, we show that deposition can be carried out over a wide pH region ranging from 1.5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(126 citation statements)
references
References 72 publications
3
123
0
Order By: Relevance
“…10 However, other electrolyte, such as NaCl and Na 2 SO 4 (Hilder et al, 2011) have been reported as supporting electrolyte in GO colloidal suspension. The electrochemical reduction process can be performed with cyclic voltammetry Jiang et al, 2012), linear sweep voltammery mode at a constant potential mode (Chang et al, 2012;Ping et al, 2011) in a standard three electrode system at ambient temperature.…”
Section: Structure and Electrochemical Aspects Of Graphene Oxide (Go)mentioning
confidence: 98%
See 1 more Smart Citation
“…10 However, other electrolyte, such as NaCl and Na 2 SO 4 (Hilder et al, 2011) have been reported as supporting electrolyte in GO colloidal suspension. The electrochemical reduction process can be performed with cyclic voltammetry Jiang et al, 2012), linear sweep voltammery mode at a constant potential mode (Chang et al, 2012;Ping et al, 2011) in a standard three electrode system at ambient temperature.…”
Section: Structure and Electrochemical Aspects Of Graphene Oxide (Go)mentioning
confidence: 98%
“…The optimal conductivity range was found to be between 4 and 25 mS cm -1 for neutral pH media (0.5 mg mL -1 GO and 0.25 M NaCl) at a reduction potential of -1.2 V with respect to saturated calomel electrode (SCE). In addition to the conductivity of the medium, the selection of the appropriate pH (1.5 -12.5) for the medium is also essential to ensure good deposition of the electrochemically reduced GO onto the electrode surface (Hilder et al, 2011).…”
Section: Structure and Electrochemical Aspects Of Graphene Oxide (Go)mentioning
confidence: 99%
“…By this means, copper NPs can be facilely synthesized on the surface of conducting surfaces, and the sizes and shapes of the prepared nanoparticles can be easily controlled by altering the conditions of electrochemical deposition [10,11]. Meanwhile, it is reported recently that high quality graphene can be prepared by electrochemical reduction of GO at −1.5 V, which eliminate the use of excessive reducing agents which will contaminate the resultant products and can completely reduce the oxygen functionalities on GO [15,16]. While the deposition of Cu NPs starts at much more positive potentials (normally at −0.25 V), it is expected that electrochemical reduction of GO and electrodeposition of Cu NPs can be simultaneously performed at −1.5 V vs. SCE in a solution of copper ion.…”
Section: Introductionmentioning
confidence: 97%
“…In all experiments reported ED was performed at 10 mVs -1 for 30 cycles. The salt concentration in solution ranged from 100 to 250 mM to provide enough ionic strength and conductivity to the electrolyte solution [16]. These conditions allow the formation of a stable GO dispersion in terms of charge and size, also allowing optimum transfer of GO particles to the electrode and their subsequent electrochemical reduction.…”
Section: Fabrication and Characterisation Of Graphene Electrodesmentioning
confidence: 99%
“…drop-casting, brushing or spraying [13][14][15]. Recently, the electrodeposition of graphene oxide and its simultaneous electrochemical reduction on the electrode surface has been proposed as a reproducible method for the fabrication of stable and high surface area electrodes [16][17][18]. 3 Graphene-based electrodes have been used for several applications, such as biosensing or as support for further immobilization of enzymes [9,10].…”
Section: Introductionmentioning
confidence: 99%